2013
DOI: 10.1179/1973947813y.0000000126
|View full text |Cite
|
Sign up to set email alerts
|

The quality of life in patients during intravesical treatment and correlation with local symptoms

Abstract: Long-term intravesical treatment could decline the QoL of patients. Local symptom was an important factor found to be associated with impairment of QoL. Appropriate therapy for local symptoms might improve the patients' overall QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 13 publications
(12 reference statements)
2
26
0
Order By: Relevance
“…Previous publications on NMIBC included 4 crosssectional studies [5,11,13,14], 2 clinical trials evaluating intravesical BCG [17,18], and 3 observational prospective studies [12,15,16]. Of the latter 3, only 2 had pretreatment and posttreatment evaluations [12,16], and none of them used bladder cancer-specific HRQL instruments. These studies showed a relevant HRQL decline after bladder cancer diagnosis [12] and after intravesical treatment [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous publications on NMIBC included 4 crosssectional studies [5,11,13,14], 2 clinical trials evaluating intravesical BCG [17,18], and 3 observational prospective studies [12,15,16]. Of the latter 3, only 2 had pretreatment and posttreatment evaluations [12,16], and none of them used bladder cancer-specific HRQL instruments. These studies showed a relevant HRQL decline after bladder cancer diagnosis [12] and after intravesical treatment [16].…”
Section: Discussionmentioning
confidence: 99%
“…Of the latter 3, only 2 had pretreatment and posttreatment evaluations [12,16], and none of them used bladder cancer-specific HRQL instruments. These studies showed a relevant HRQL decline after bladder cancer diagnosis [12] and after intravesical treatment [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The core lower urinary tract symptom score (CLSS) questionnaire was recently developed by Dr Homma's group, and had been used as a reliable instrument for lower urinary tract symptoms (LUTS) assessment in several studies . However, the psychometric properties of the CLSS still need to be further evaluated.…”
mentioning
confidence: 99%
“…9,10 Currently there are only a few published studies regarding HRQOL in NMIBC population and the authors of the present study contemplate to evaluate this specific point in their next series. [11][12][13][14][15][16][17][18] (MIBC)…”
Section: Introductionmentioning
confidence: 99%